The Steel Industry of Brazil and Argentina. From its Creation to its Privatization (Global Journals of Research in Engineering, 2022)
The objective of this work will be to compare the impact of the development of the state steel industry in Brazil and Argentina, analyzing multiple aspects from politics, economics and society. To carry out the work, the Minutes and Reports of the companies and research prepared by different authors, knowledgeable about the steel industry in Brazil and Argentina, were used. First, we consider the international political and economic context that prompted the governments of Brazil and Argentina to develop their own steel industry. Then, we observe the beginning of the large steel companies and their population impact on the small cities where they were installed. Finally, we studied the privatizations of these companies and drew some comparative conclusions between the Brazilian steel system and the Argentine steel plan.
Keywords: brazil; argentine; steel industry; population impact; privatizations